Robustness evaluation of the chromatographic method for the quantitation of lumefantrine using Youden's test - Isabela da Costa César; Gerson Antônio Pianetti (Universidade de São Paulo, 2009)
Youden's test is a reliable method to evaluate the robustness of analytical methods, by means of an experiment design which involves seven analytical parameters combined in eight tests. In the present study, we assessed the robustness of a chromatographic method to quantify lumefantrine in raw material samples, using Youden's test. Hence, it was possible to determine the effect of each analytical parameter in the final analysis results. Youden's test showed to be a simple and feasible procedure to evaluate the robustness of chromatographic methods. O teste de Youden constitui um método confiável para avaliação da robustez de métodos analíticos, por meio de um delineamento que envolve sete parâmetros analíticos combinados em oito experimentos. No presente estudo, a robustez de um método cromatográfico para quantificação de lumefantrina em matéria-prima farmacêutica foi avaliada utilizando-se o teste de Youden. Assim, foi possível determinar o efeito de cada parâmetro analítico nos resultados finais das análises. O teste de Youden se mostrou um procedimento simples e confiável para a avaliação da robustez de métodos cromatográficos.